2021
DOI: 10.1177/09544062211048179
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate heat transfer study of hypersonic flow past a cylindrical leading edge composed of functionally graded materials

Abstract: Aero-thermodynamic analysis of a cylindrical leading edge placed in a hypersonic stream is carried out using an in-house developed conjugate heat transfer (CHT) solver. Isotropic and functionally graded materials (FGM) are tested as heat shields to understand the effects of the material property on the flow structure and aerodynamic heating associated with the mutual coupling of fluid flow and heat transfer. A simplified partitioned approach is employed to couple the independently developed fluid flow and heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…As part of code validation studies, Peetala et al 19 performed CHT analysis for different hypersonic cases including the case of cylindrical leading edge. In a recent study, John et al 20 carried out investigations to explore the coupling effect of fluid flow and heat transfer in computing the surface heatflux over a cylindrical leading edge placed in a hypersonic flow. This study revealed that the interface heatflux is a strong function of material properties of the solid domain.…”
Section: Introductionmentioning
confidence: 99%
“…As part of code validation studies, Peetala et al 19 performed CHT analysis for different hypersonic cases including the case of cylindrical leading edge. In a recent study, John et al 20 carried out investigations to explore the coupling effect of fluid flow and heat transfer in computing the surface heatflux over a cylindrical leading edge placed in a hypersonic flow. This study revealed that the interface heatflux is a strong function of material properties of the solid domain.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal post-buckling of functionally graded cylindrical shell with temperature-dependent properties was studied by Shen [35], and he also studied the post-buckling behavior of functionally graded plate [36]. The mechanical buckling and thermal post-buckling of functionally graded shear plate with temperature-dependent properties were studied by Duc and Tung [37,38], and they also gave the solution of the convective heat transfer steady-state thermal stress of ceramic/metal functionally graded EFBC composite plate with temperature-dependent material properties. Considering the practical applications of nonuniform temperature rise field in engineering structures, many scholars have studied the linear and nonlinear elastic instability deformation behaviors of functionally graded structures [39][40][41].…”
Section: Introductionmentioning
confidence: 99%